Application and Prospect of Smart Health Technologies for Optimizing the Healthcare-seeking Behaviors in Chronic Disease Patients - Yun CHEN, Weijie XU, Huaigu TIAN, Wenxin WANG (Zhongguo quanke yixue, 2022)
Smart health technologies have been increasingly used in chronic disease management, and become an important way foroptimizing the health management behaviors in patients with chronic diseases. Based on a review of studies about healthcare-seeking behaviors in Chinese patients with chronic diseases and the framework of the Andersen's Behavioral Model of Healthcare Utilization, we summarized that healthcare-seeking behaviors in these patients are associated with predisposing, enabling, and need factors, with enabling factors (economic status and education level) being the key determinant. Therefore, it is necessary to utilize the advantages of care delivery modes using smart health technologies to integrate media resources for health knowledge education, strengthen the social support for vulnerable groups and optimize the cooperation between multiple care delivery groups. The implementation of these strategies will contribute to the empowerment of people with chronic diseases, optimizing their healthcare-seeking behaviors, and making effective use of health service resources.